The Use Of The Fishbowl Technique In Teaching English Speaking Skills: A Library Research Study - Stesia Abigael Tombo; Darmawan Darmawan; Wahyudin Wahyudin (Hasanuddin University, 2026)
This study aims to analyze previous research on the implementation of the Fishbowl Technique in teaching speaking skills. Specifically, the study seeks to examine how the Fishbowl Technique is applied in speaking instruction across different educational levels and to identify its effects on students’ speaking performance. This research employed a qualitative library research design by reviewing five scientific studies published between 2019 and 2025. The selected studies were analyzed to identify common practices, variations in implementation, and reported outcomes related to the use of the Fishbowl Technique. The results of the analysis indicate that the Fishbowl Technique was implemented in similar ways across the reviewed studies, although minor differences were found in classroom procedures and student grouping. In general, the technique provided structured opportunities for students to speak actively while other students observed and learned from the interaction. The findings show that the Fishbowl Technique had a positive impact on students’ speaking skills, particularly in improving fluency, participation, and confidence. Students became more willing to express their ideas and engage in classroom discussions. Overall, the reviewed studies demonstrate that the Fishbowl Technique effectively promotes active speaking practice and enhances classroom interaction, making it a beneficial strategy for teaching speaking skills.